Variations in physico-chemical and antioxidant attributes of grape seed oil as function of extraction techniques - Shaukat, Usman Ali; Anwar, Farooq; Akhtar, Muhammad Tahir; Qadir, Rahman; Zahoor, Sadaf; Saba, Iram; Shabir, Ghulam; Siddique, Farzana; Anuchita Moongngarm (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aim of the current research work was to assess and compare the impact of two extraction techniques on the physico-chemical, and antioxidant parameters of grape seed oil (GSO). The GSO extracted by Soxhlet and Folch methods indicated a notable variation in the oil yield (8.58 % and 10.19%) and saponification value (196.35 and 189.33 mg of KOH g-1), respectively. However, no significant (p<0.05) variation was detected for density, acid value, refractive index, iodine no, unsaponifiable matter, and free fatty acids between the tested two oils. Meanwhile, the oil produced by Soxhlet method exhibited relatively a higher extent of unsaturated dienes, trienes, peroxide value, p-anisidine value, and thus poor oxidation state. A notable variation in the content of principal fatty acid (linoleic acid) was recorded between Folch extracted oil (70.11%) and Soxhlet extracted oil (66.57%). The contents of total tocopherols were noted to be considerably higher for Folch extracted oil (105.55 mg kg-1) than the Soxhlet extracted oil (73.70 mg kg-1). Among the individual phenolics analyzed by HPLC, gallic acid (14.02 mg kg-1) and caffeic acid (5.20 mg kg-1) were detected as major component in Folch extracted oil and Soxhlet extracted oil, respectively. The results of the present comparative study support that Folch method is relatively a good choice for the extraction of GSO with promising nutritive quality in terms of oxidation parameters, contents of linoleic acid and antioxidant phenolics.